Paramedic’s Trust and Compliances during COVID-19 Preparedness and Recovery Time - Wasisto, Aryo (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
High trust in government’s capability is the key to public compliance in supporting COVID-19 management. The paramedic is a profession that has received attention during times of pandemics because they are on duty as frontlines with a high risk of transmission. This research analyzed a survey of 328 paramedics living in Jakarta to examine their perceptions of the COVID-19 pandemic, the government's readiness, the picture of their psychological condition, their trust in the government, and their belief in themselves in health services. The survey was conducted one week after WHO declared COVID-19 a pandemic. This descriptive study indicates that most respondents have serious concerns about the transmission of the virus. On the side, they are obliged by an oath of service, which demands that they are always ready to serve. Only 30% believe the government can handle COVID-19. All respondents strongly supported the "lockdown" policy in every public facility. This finding is consistent with interview data after the highest peak of COVID-19 transmission in September 2021.These findings also point that low trust is driven by inconsistent and less convincing communication of political officials. Despite paramedics' risky conditions, they are responsible for working, but paramedics at the forefront of handling COVID-19 patients require support policies such as higher incentives and the safest protective tools.